The spike characteristics of winter wheat (Triticum aestivum L.) varieties in agro-ecological conditions of Banja Luka region - Kondić Danijela; Bajić Maja; Hajder Đurađ; Knežević Desimir; Bosančić Borut (Agroznanje, 2017)
The aim of this study was to analyze the spike length, number of grains per spike and grain weight per spike of winter wheat in agro-ecological conditions of Banja Luka at different sowing densities. Three winter wheat varieties (NS 40S, Prima and Nova Bosanka) were examined at seven sowing densities (384, 424, 451, 504, 544, 588 and 604 seeds/m2 ) in two growing seasons (2013/14 and 2014/15). Experimental design was a completely random system with four replications. In all wheat varieties, sowing was carried out from the 6th to 8th November in 2013/14 and from the 3rd to 5th November in 2014/15. Sampling of plants was done in the first decade of July in both experimental years. Factorial ANOVA 2×8×3 and LSD-test were performed, with year, sowing density and variety as main factors. For different varieties, the average number of grains per spike ranged from 34.53 to 38.19 while the average grain weight per spike (g) ranged from 1.58 to 1.73 g. The spike length ranged from 7.58 to 8.20 cm for varieties with statistically significant interaction effect variety × year at P ≤ 0.01. Spike parameters were generally higher in the second experimental year (2014/15).